Avaliação dos conhecimentos teóricos sobre tabagismo a partir de duas intervenções educativas em escolares do ensino fundamental - Silva, Daniela Tomazini da (2007)
The objective of this study was to verify the changes of theoretical knowledge relating to smoking, valued at two points (pre and post tests) considering two speeches education (classroom and exhibition group operating). 68 subjects were students of both sexes, three% nd series of primary school, a public school, the city of Bauru. To achieve the proposed objective were evaluated previous knowledge (M1) of the students about the matter and then was applied a procedure for teaching expositivo in G1 and G2 operating a program of games and G3 any intervention. Finally, a revaluation was performed (M2) of the theoretical knowledge of the participants for analysis of the percentage of correct on theoretical knowledge relating to smoking, at times, was used the Wilcoxon test and the individual comparisons in the pre - and post-test and the razlike between their moments was the Kruskal-Wallis. In comparing the respective moments of assessment found that the G1 obtained when 1 (Md = 3) and 2 (Md = 4.50), with statistically significant difference (p <0.0001), the G2 when 1 (Md = 2) and 2 (Md = 4), with statistically significant difference (p <0.0001) and G3 when 1 (Md = 3) and 2 (Md = 2), which he does not result showed statistically significant (p> 0.05). In comparisons among groups at the pre-test, it was found that there is no statistically significant difference between groups (p> 0.05). Comparing the groups after the completion of the programme (post-test), it was found that the group G1 had greater knowledge regarding the G3 group (p <0001). The groups G1 and G2, did not differ statistically between themselves and the group G2 compared to group G3 (p> 0.05). Comparisons made by the difference between the moments of the groups showed significant results G1 and G2 compared to the control group (p <0.0001), however, when compared with each other showed no statistically significant difference.